The Political Economy of Inclusive Growth : A Review. (IMF Working Papers; Working Paper ;, 2021)
In this paper, we review the role of the political economy in inclusive growth. We find that political economy forces on the demand and supply side have weakened redistribution over time and contributed to a new wave of populism. We document growing support for a rethink of the social contract to make growth more inclusive and discuss some of its broad elements.